Sex hormones and the risk of myocardial infarction in women and men: a prospective cohort study in the UK Biobank - Katie Harris; Sanne A. E. Peters; Mark Woodward (Biology of Sex Differences, 2023)
Abstract Objectives There is conflicting evidence around the role of sex hormones with cardiovascular outcomes. The aim of this study was to examine the association of sex hormones with the risk of myocardial infarction (MI) in pre- and post-menopausal women, and men in the UK Biobank. Methods The UK Biobank is a prospective population-based cohort study, that recruited over 500,000 (aged 40–69 years) women and men between 2006 and 2010. Sex specific cox regression models, estimating hazard ratios (HRs) and women to men ratio of HRs (RHR) with respective 95% confidence intervals (CI), were used to model the association of sex hormones [oestrogen, testosterone, oestrogen: testosterone (O/T) ratio, sex hormone–binding globulin (SHBG) and the free androgen index (FAI)], measured at study baseline, with incident MI for women and men. Results Data were from 479,797 participants [264,282 (55.1%) women] without a history of MI at study baseline. Over 12.5 years of follow-up, there were 4,908 MI events in women and 10,517 in men. Neither oestrogen nor testosterone were associated with MI in women and men after multiple adjustment. For men, but not women, a unit higher log-transformed O/T ratio was associated with a lower risk of MI 0.79 (0.65, 0.95) after adjustment for traditional CVD risk factors. The corresponding women to men RHR (95% CI) was 1.24 (0.99, 1.56). Higher SHBG (per unit) was also associated with a lower risk of MI in men 0.94 (0.89, 0.99), and not in women 1.02 (0.95, 1.09) after multiple adjustment, the corresponding women to men RHR (95% CI) was 1.09 (1.00, 1.18). Higher FAI was associated with a higher risk of MI in men 1.09 (1.02, 1.15), though not in women 0.97 (0.92, 1.02), the corresponding women to men RHR was 0.89 (0.82, 0.97). Finally, there were differential effects in the association of SHBG and FAI between pre- and post-menopausal women. Conclusions A higher O/T ratio was associated with a lower risk of MI, and a higher FAI with a higher risk of MI after adjustment for CVD risk factors in men, but not in women. Thus, hormone ratios, rather than each alone, may play an important role in modulating the effect of MI.